The road to Durban and beyond: The progress of international climate change negotiations - Macey, Adrian (New Zealand Science Review, 2012)
Following a familiar pattern of UN climate change negotiations, the 2011 Durban conference of the parties (COP17) was concluded by sleep-deprived delegates well after its scheduled end, after crises and last-minute drama. Just what it might mean for the future was not immediately obvious to observers. Early reactions ranged from seeing yet another failure by governments to grasp the seriousness and urgency of climate change – ‘a disaster for us all’ – to much more positive assessments. The executive secretary of the United Nations Framework Convention on Climate Change (UNFCCC), Christiana Figueres, described Durban as ‘without doubt ... the most encompassing and furthest reaching conference in the history of the climate change negotiations’. To make sense of the outcome, it helps to view the short history of these negotiations through a political lens. Each conference of the parties, besides whatever operational decisions it takes and work programmes it initiates, is a snapshot of the international community’s political take on climate change. In this sense, Durban can be seen as the product of Montreal (2005), Bali (2007), and Copenhagen (2009) COPs, with clear political steps forward every two years. That is not to say the intervening COPs, Nairobi (2006), Poznań (2008), and Cancún (2010) made no contribution. They all helped advance the negotiations; Cancún indeed probably saved the multilateral process. But the intervening COPs lacked the political impact of the others, and produced no new framing of the negotiations.